The Influence of Digital Advertising and Brand Awareness on Sales of Micro and Medium Enterprise Products Selling in Southern Borneo - Joe Ananda; Ullyia Akbar; Tina Lestari (Jurnal Ilmiah Bisnis dan Ekonomi Asia)
This study aims to examine the influence of digital advertising on micro, small, and medium-sized enterprises (MSME’s) in South Borneo. This study employed a quantitative approach using the Slovin method and random sampling. In order to conduct this study, the distribution of questionnaires through Google Forms is restricted in Banjarmasin and Banjarbaru only. The data collected was a total of 405 respondents, and with the use of the Slovenian method, 397 respondents were used as samples for this study. Data from the questionnaire are in process and calculated using SPSS version 27. In the practical and efficient 21st century, technology has become a primary necessity for everyone. The study aims to see how efficient the use of digital marketing is for entrepreneurs and invites people who have not yet used the technology in selling their products or services to start using it. The goal is to reach even wider markets and reach a wide range of customers everywhere